The frontier and religion : a comparative study of the United States of America and South Africa in the first half of the nineteenth century - Boucher, M; Bradlow, Edna; Stals, E. L. P (Stellenbosch : Stellenbosch University, 2012)
Boucher's contribution originally published as MA thesis, University of South Africa.